A In-VITRO ANTIBACTERIAL ACTIVITY OF NEEM LEAF ETHANOL EXTRACT (Azadirachta Indica A. Juss) AGAINST THE FUNGI Candida albicans: In-VITRO AKTIVITAS ANTIBAKTERI EKSTRAK ETANOL DAUN MIMBA (Azadirachta Indica A. Juss) TERHADAP JAMUR Candida albicans - Khairi, Widayatul; Hendriyani, Irmatika; Safwana, Safwan (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) UNIVERSITAS JENDERAL ACHMAD YANI YOGYAKARTA, 2025)
Background: Infections are common diseases in tropical regions, including Indonesia. One of the most frequently encountered causes of infection is fungal infection by the Candida albicans species. Infections caused by Candida albicans are known as candidiasis, which is an acute or subacute fungal disease that can affect various areas such as the mouth, vagina, skin, nails, lungs, and digestive tract. Objective: This study aims to examine whether the ethanol extract of neem leaves (Azadirachta indica A. Juss) has antifungal properties that effectively inhibit the growth or kill Candida albicans, as indicated by the diameter of the inhibition zone. Method: The study utilized the well diffusion method, and the concentrations used were 80%, 40%, 20%, 10%, and 5%, with each concentration tested in triplicate. Results: The research findings showed that the inhibition zone diameters for each concentration were as follows 5%: 2.33±1.26 mm; 10%: 4.85±0.30 mm; 20%: 4.66±0.58 mm; 40%: 6.06±0.03 mm; dan 80%: 12.88±9.87 mm. Additionally, phytochemical screening confirmed that the ethanol extract of neem leaves (Azadirachta indica A. Juss) contained alkaloids, flavonoids, tannins, saponins, and steroids. Conclusion: The study concluded that the highest inhibition zone diameter against Candida albicans was observed at the 80% concentration, measuring 12.88±9.87 mm.